Optimizing colorectal polyp detection and localization: Impact of RGB color adjustment on CNN performance - Jirakorn Jamrasnarodom; Pharuj Rajborirug; Pises Pisespongsa; Kitsuchart Pasupa (MethodsX, 2025)
-scores on both internal and external validation datasets.
Keywords: Colorectal Cancer Screening and Detection; Advanced Neural Network Applications; Radiomics and Machine Learning in Medical Imaging